Pengaruh Faktor Internal Perusahaan terhadap Islamic Social Reporting (ISR) pada Bank Umum Syariah Indonesia Periode 2018-2023 - Kusuma, Bryan Ranu; Ruhana, Nafisah; Nurdin, Ade Ali (Journal of Applied Islamic Economics and Finance, 2024)
This research examines the effects of firm SIZE, Leverage, profitability, and the number of Sharia Supervisory Board (DPS) members on Islamic Social Reporting (ISR) disclosure in Indonesian Full-Fledged Islamic Bank during the period 2018-2023. Using panel data regression analysis with a purposive sample of 11 Sharia banks registered with the Financial Services Authority (OJK), the study found that all four independent variables collectively influence ISR disclosure. Specifically, firm SIZE has a significant positive effect, while the number of DPS members has a significant negative effect. Leverage and profitability do not exhibit significant influence. These results imply that management in Full-Fledged Islamic Bank should focus on total asset management and enhance Standard Operating Procedures (SOPs) related to the roles and responsibilities of the DPS to improve ISR disclosure quality.